Novel BRCA1 and BRCA2 Tumor Test as Basis for Treatment Decisions and Referral for Genetic Counselling of Patients with Ovarian Carcinomas. Issue 2 (9th November 2016) - Weren, Robbert D.A.; Mensenkamp, Arjen R.; Simons, Michiel; Eijkelenboom, Astrid; Sie, Aisha S.; Ouchene, Hicham; van Asseldonk, Monique; Gomez‐Garcia, Encarna B.; Blok, Marinus J.; de Hullu, Joanne A.; Nelen, Marcel R.; Hoischen, Alexander; et al.
Abstract : To improve hereditary cancer risk assessment and clinical treatment (e.g., PARP‐inhibitors) of (ovarian) cancer patients, we have developed a method for rapid and reliable detection of mutations affecting BRCA1 and BRCA2 using single‐molecule molecular inversion probe‐based targeted next‐generation sequencing on formalin fixed tissue. By targeting both DNA strands and including single molecule tags, this method proved to reliably detect both germline and somatic mutations in BRCA1 and BRCA2 in DNA derived from FFPE ovarian carcinomas. ABSTRACT: With the recent introduction of Poly(ADP‐ribose) polymerase inhibitors, a promising novel therapy has become available for ovarian carcinoma (OC) patients with inactivating BRCA1 or BRCA2 mutations in their tumor. To select patients who may benefit from these treatments, assessment of the mutation status of BRCA1 and BRCA2 in the tumor is required. For reliable evaluation of germline and somatic mutations in these genes in DNA derived from formalin‐fixed, paraffin‐embedded (FFPE) tissue, we have developed a single‐molecule molecular inversion probe (smMIP)‐based targeted next‐generation sequencing (NGS) approach. Our smMIP‐based NGS approach provides analysis of both strands of the open reading frame of BRCA1 and BRCA2, enabling the discrimination between real variants and formalin‐induced artefacts. The single molecule tag enables compilation of unique reads leading to a high analytical sensitivity and enabling assessment of the reliability of mutation‐negative results. Multiplex ligation‐dependent probe amplification (MLPA) and Methylation‐specific multiplex ligation‐dependent probe amplification (MS‐MLPA) were used to detect exon deletions of BRCA1 and methylation of the BRCA1 promoter, respectively. Here, we show that this combined approach allows the rapid and reliable detection of both germline and somatic aberrations affecting BRCA1 and BRCA2 in DNA derived from FFPE OCs, enabling improved hereditary cancer risk assessment and clinical treatment of ovarian cancer patients.